Strategic Purchasing: Lessons from Four Country Assessments in Burkina Faso, Colombia, Karnataka (India) and the Philippines - Aurélie Klein; Vergil de Claro; Narayanan Devadasan; Joël Arthur Kiendrébéogo; Juan Carlos Rivillas (The Collectivity - Institute of Tropical Medicine, 2018)
More low- and middle-income countries seek to shift to strategic purchasing, creating a demand for practical tools to assess current purchasing situations and identify options for future development. To contribute to such processes, a collectivity group on Strategic Purchasing and Universal Health Coverage was launched jointly by the World Health Organization (WHO), the Institute of Tropical Medicine Antwerp, and the Communities of Practice on Performance-Based Financing and Financial Access to Health Services. Four country assessments were conducted to explore how the weaknesses in purchasing set-ups affect UHC intermediate and final objectives as well as other effects on the health system. The assessments were complemented with literature review, interviews and discussions with key stakeholders, quantitative data collection. They were conducted between March - July 2018 in Burkina Faso, Colombia, Katarnaka (India), and the Philippines.
Keywords: 330; strategic purchasing; universal health coverage; Burkina Faso; Colombia; Katarnaka (India); Philippines